Design and Construction of Measuring the Height Underground Tank SPBU Using Raspberry Pi - Irahadiputra, Wisnu Franca; Fadli, Abdul (Association for Scientific Computing Electrical and Engineering (ASCEE), 2022)
A fuel Station or commonly abbreviated as a gas station, is a place to refuel motor vehicles. At gas stations, there are submersion tanks to store oil reserves. In checking, it is still used manual method. The manual method that is still carried out today is considered less efficient in terms of time and accuracy of measuring instrument readings. Moreover, nowadays, it is possible to create digital measuring instruments. In this study, a digital measuring instrument will be designed using raspberry pi. In this study, a prototype of a tubular gas station submersion tank will be made. The measuring instrument consists of raspberry pi as the main processor of the system, using HCSR04-type ultrasonic sensor and LCD as the result viewer. From the research that has been made, a prototype of a submersion tank with dimensions of 60 cm long and 30 cm in diameter has been made. Volume analyzers are able to read with an error percentage of 0.9% in horizontal tube testing and 0.6% in vertical tube testing. The prototype of the gas station submersion tank as an oil container was successfully made and measured in volume by a digital measuring instrument using raspberry pi.